Analysis of Domestic Waste Water Systems as a Sustainable Development Goals Achievement (SDGs) in Settlements in Bulak District, Surabaya City - Andri Deka Lisiadi; Rooslan Edy Santosa (IJESEMS : International Journal of Engineering Science Educatioon and Management System, 2018)
Water is an essential substance for life because the body of living things mostlyconsists of water, except for living things in the form of seeds, and spores.Water used by humans undergoes changes in chemical and physical properties.The complex problem that is often overlooked by the government and society is domestic wastewater caused by population growth and building developments in the city of Surabaya. This study used an interview technique (with a questionnaire instrument) and observation interviews. From the results of direct observation and interviews found the number of families who have and use private latrines by 99 respondents and only one respondent who wearspublic toilet. 99.5% of respondents have sewerage and only 0.5% of respondents who do not have.